2020
DOI: 10.3390/coatings10090848
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Synergistic Effect of Chitosan/Sodium Phytate/MgO Nanoparticle Fire-Retardant Coatings on Wood Substrate through Layer-By-Layer Self-Assembly

Abstract: Fire-retardant chitosan/sodium phytate/MgO nanoparticle (CH/SP/nano-MgO) coatings were loaded on a wood substrate via electrostatic layer-by-layer self-assembly and characterized by scanning electron microscopy and energy-dispersive spectrometry. The flammability and thermal degradation of the original wood and wood samples treated with chitosan, chitosan/sodium phytate, chitosan/sodium phytate/MgO nanoparticles were studied by limiting oxygen index (LOI), exposure combustion experiments and thermogravimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, this approach has to be considered as performance is satisfactory for material with only one side exposed to a fire and is more industrially viable. Comparison with LbL systems is difficult as, to the best of authors’ knowledge, no cone calorimeter measurements have been taken for them [ 17 , 32 , 76 ]. PEC deposition with PEI and sodium hexametaphosphate resulted in a 10% pHRR reduction following a one hour of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach has to be considered as performance is satisfactory for material with only one side exposed to a fire and is more industrially viable. Comparison with LbL systems is difficult as, to the best of authors’ knowledge, no cone calorimeter measurements have been taken for them [ 17 , 32 , 76 ]. PEC deposition with PEI and sodium hexametaphosphate resulted in a 10% pHRR reduction following a one hour of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…SPA is highly water soluble, making it an interesting polyelectrolyte for fire retardancy. Its deposition by LbL application and sol-gel processes has been studied on various substrates [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], including wood [ 17 , 32 ]. Wood has also been impregnated with phytic acid to improve fire retardancy [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later, until recent years, LBL self-assembly technology was applied on wood surfaces for flameproof modification. Zhao constructed a CS/sodium phytate/MgO nanoparticle coating on wood substrates via electrostatic LBL self-assembly and endowed wood with certain fire retardancy, 23 while Zhou used a similar method to load a CS/sodium phytate/TiO 2 –ZnO nanoparticle coating on wood. 24 However, both of these two coatings built using polyelectrolytes and metal oxide composite systems did not show satisfactory flame-retardant performance, and the limited oxygen indexes (LOIs) were only around 33.…”
Section: Introductionmentioning
confidence: 99%
“…Studies researching the relationship between the dynamic modulus of elastic (MOEd) and the static modulus of elastic (MOEs) have primarily used the transverse vibration method, the vertical vibration method, the ultrasonic wave method, the stress wave method, etc. (Mohammad and Mohsen 2017;Bi et al 2020;Zhao et al 2020;Fu et al 2021). Previous studies showed that correlation between the MOEd and MOEs was relatively higher when using the transverse vibration method compared to other methods (Bi et al 2020;Fu et al 2021).…”
Section: Introductionmentioning
confidence: 99%